Unraveling timing uncertainty of event-driven connectedness among oil-based energy commodities - Daniel Bartušek; Evžen Kočenda (Charles University in Prague, Institute of Economic Studies (IES), 2023)
The pricing dynamics of oil-based commodities are frequently influenced by reported events. Our analysis spans almost 900 oil-related events from 1978 to 2022, categorizing them based on recurring characteristics. Employing a novel bootstrap-after-bootstrap testing econometric framework, we quantify dynamic connectedness among energy commodities. Our findings reveal over 20 statistically significant historical events that triggered abrupt and enduring increases in volatility connectedness. Notably, geopolitical events are more consistently associated with elevated connectedness than economic events, while natural events do not exhibit a similar impact. The prevailing characteristics shared by events leading to increased volatility connectedness include their negativity, unexpected nature, and the introduction of concerns about oil supply shortages.
Keywords: C32; C58; G15; Q02; Q35; 330; energy commodities; crude oil; volatility connectedness; systemic events; bootstrapafter-bootstrap procedure